2020
DOI: 10.1109/lra.2020.2969200
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark for Human-to-Robot Handovers of Unseen Containers With Unknown Filling

Abstract: The real-time estimation through vision of the physical properties of objects manipulated by humans is important to inform the control of robots for performing accurate and safe grasps of objects handed over by humans. However, estimating the 3D pose and dimensions of previously unseen objects using only RGB cameras is challenging due to illumination variations, reflective surfaces, transparencies, and occlusions caused both by the human and the robot. In this letter, we present a benchmark for dynamic human-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…There are many concrete applications, where a robot has proven to be useful in helping humans by handing over objects, such as short-cycle repetitive tasks [67] or dynamic object handover tasks [68,69]. In the last decade, some studies described the process of object handover between humans with the purpose of transferring that same execution to robots [70,71].…”
Section: Object Handovermentioning
confidence: 99%
See 2 more Smart Citations
“…There are many concrete applications, where a robot has proven to be useful in helping humans by handing over objects, such as short-cycle repetitive tasks [67] or dynamic object handover tasks [68,69]. In the last decade, some studies described the process of object handover between humans with the purpose of transferring that same execution to robots [70,71].…”
Section: Object Handovermentioning
confidence: 99%
“…Bi-directional [67,72] Fluent Movements (Human-like) [68,72,76,83,84] Learning [68,74,77,[93][94][95] Give/Receive Moving Object [68,69] Object Possession decision contact point…”
Section: Object Handovermentioning
confidence: 99%
See 1 more Smart Citation
“…In [12], a benchmark is provided for assessing aerial manipulation capabilities, e.g., aerial grasping, force control etc. The work in [13] focuses on dynamic human-to-robot handovers, and provides experimental procedures for transferring cups with different fullness levels and transparencies. The work in [14] provides a framework to assess the performance of robotic manipulation simulators via a real-world dataset.…”
Section: E Other Benchmarksmentioning
confidence: 99%
“…Let us imagine a robot which is asked to receive a glass of water from a human: it should recognize the human carefulness to manipulate the glass without spilling water. The carefulness has been explored in studies of human-human handovers to teach robots how to correctly transfer objects [12,3], monitoring human movements with motion capture sensors. In a previous study, we demonstrated that it is possible to train a classifier to distinguish between careful and non careful human motions using only data from a low-resolution camera [7].…”
Section: Introductionmentioning
confidence: 99%